A haemopneumothorax revealing thoracic endometriosis - Khalil Ghebouli; Abdelnacer Haddam; Amar Djender; Mohammed Amine Kecir; Mehdi Belbekri; Sedik Merouani; Houda Amrane; Kenza Bendjoudi (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2024)
Thoracic endometriosis is a rare disease but its actual frequency may be underestimated. Optimal management remains controversial. A multidisciplinary management approach, including surgery and hormone therapy, seems to give the best results and reduces recurrence. We report a case of a patient presenting with recurrent haemopneumothorax caused by thoracic endometriosis and treated surgically by video thoracoscopy and hormonal treatment.